Pengaruh Kurs, Deposito Dan BI Rate Terhadap Kredit (Studi Empiris Pada Bank Umum Di Indonesia) - Mochamad Taufiq; Marius Pramana; Anastasia Lipursari (Universitas Diponegoro, 2024)
AbstractThe purpose of this research is to analyze the effect of exchange rate, deposit and BI rate on credit. The population in this study is all monthly data from the exchange rate, BI rate, deposits, and credit of conventional commercial banks in Indonesia. The sampling method is purposive sampling with the criteria used being the closest (up to date) period by taking available data from January 2014 to December 2023. The results of hypothesis testing show that hypothesis 1 (H1) that the exchange rate has a negative effect on credit is not proven and cannot be interpreted. Hypothesis 2 (H2) that deposits have a positive effect on credit is proven and can be interpreted that an increase in the amount of deposits will increase the amount of credit. Hypothesis 3 (H3) that the BI rate has a negative effect on credit is proven and can be interpreted that an increase will reduce the amount of credi, increase in the BI rate will decrease credit. Keywords: Exchange rates, deposits, BI rate, credit.